2008
DOI: 10.1111/j.1365-2923.2008.03109.x
|View full text |Cite
|
Sign up to set email alerts
|

Medical students' experiences with medical errors: an analysis of medical student essays

Abstract: There are many missed opportunities to teach students how to respond to and learn from errors. Some faculty members and housestaff may at times respond to errors in ways that appear to contradict professional standards. Medical educators should increase exposure to exemplary responses to errors and help students to learn from and cope with errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 23 publications
4
68
0
6
Order By: Relevance
“…Nursing samples were also consistent in raising a feeling of personal responsibility for an error and the commitment to reporting such incidents regardless of an increased likelihood of being blamed 14 24 26 30. Papers featuring trainee samples highlighted the learning element of making an error, focussing on clinical outcomes and change in practice 16 19 31 34. All studies that explored only adverse events, or the most memorable or significant error, included samples limited to physicians, resulting in increased focus on the activities taken to manage the clinical outcomes of the error and professional repercussions of these events 15 22 29 32 35.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Nursing samples were also consistent in raising a feeling of personal responsibility for an error and the commitment to reporting such incidents regardless of an increased likelihood of being blamed 14 24 26 30. Papers featuring trainee samples highlighted the learning element of making an error, focussing on clinical outcomes and change in practice 16 19 31 34. All studies that explored only adverse events, or the most memorable or significant error, included samples limited to physicians, resulting in increased focus on the activities taken to manage the clinical outcomes of the error and professional repercussions of these events 15 22 29 32 35.…”
Section: Resultsmentioning
confidence: 92%
“…Individuals may function at the expected performance level but continue to be disturbed by the error event, where others may experience enhanced performance as a result of actively engaging in improving practice after a negative clinical incident 17. The importance of handling error in the correct way with a trainee sample was also highlighted, that is, avoiding punitive action or negative responses 21 31. Wolf et al suggested that the inadequate management of error resulted in less learning, and poorer coping going forward 27…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Students should be helped to learn from and cope with medical errors [42] and should see in real time how teams and leaders take accountability for medical errors and full disclosure. Teaching has been shown to improve learners' knowledge, skills, and attitudes to error disclosure [43].…”
Section: Implications Of Professional Self-regulation For Educationalmentioning
confidence: 99%